2015
DOI: 10.1016/j.epsl.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic matter on the adsorption of 210Pb, 210Po and 7Be and their fractionation on nanoparticles in seawater

Abstract: Editor: J. Lynch-StieglitzKeywords: radionuclide scavenging natural organic matter nanoparticles polonium lead beryllium Improved applications of 210 Po, 210 Pb and 7 Be as geochemical proxies require more detailed understanding of their interactions with particles. Here, laboratory sorption experiments were carried out to examine the adsorption of 210 Po, 210 Pb and 7 Be and their fractionation on inorganic nanoparticles, including SiO , in the presence or absence of macromolecular organic compounds (MOCs) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…In addition, a few studies on hydrothermal plumes indicate that hydrothermal particles favor the interactions between Fe and dissolved organic matter [ Toner et al ., ], and this interaction increases the delivery of POC from the hydrothermal plume to the sediments [ German et al ., ]. Controlled experiments also reveal the adsorption of dissolved organic carbon (DOC) onto Fe/Mn (hydr)oxides [ Yang et al ., ]. A series of studies suggests that the DOC in seawater, including marine exopolymeric substances [ Quiroz et al ., ; Zhang et al ., ], acid polysaccharide [ Quigley et al ., ], proteins, total carbohydrates, and uronic acids [ Chuang et al ., ], has numerous binding ligands which can combine with 234 Th.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a few studies on hydrothermal plumes indicate that hydrothermal particles favor the interactions between Fe and dissolved organic matter [ Toner et al ., ], and this interaction increases the delivery of POC from the hydrothermal plume to the sediments [ German et al ., ]. Controlled experiments also reveal the adsorption of dissolved organic carbon (DOC) onto Fe/Mn (hydr)oxides [ Yang et al ., ]. A series of studies suggests that the DOC in seawater, including marine exopolymeric substances [ Quiroz et al ., ; Zhang et al ., ], acid polysaccharide [ Quigley et al ., ], proteins, total carbohydrates, and uronic acids [ Chuang et al ., ], has numerous binding ligands which can combine with 234 Th.…”
Section: Discussionmentioning
confidence: 98%
“…Previous laboratory studies have also suggested that Pb and Th can be strongly adsorbed onto magnetic minerals (e.g., hematite and magnetite; Murphy et al, ; Rajput et al, ). The relationship between excess 210 Pb ( 210 Pb ex ), excess 234 Th ( 234 Th ex ), and the χ ARM /SIRM ratio exhibited no regional differences because 234 Th ex and 210 Pb ex have stronger affinities for lithogenic particles and are less affected by organic matter in comparison to other radionuclides (e.g., 7 Be; Geibert & Usbeck, ; Yang et al, ). However, the relationship between 7 Be and the χ ARM /SIRM ratio differed between the southern and northern regions of the study area (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the relationship between 7 Be and the χ ARM /SIRM ratio differed between the southern and northern regions of the study area (Figure ). The transfer of atmospheric 7 Be to sediments can be influenced by organic matter or lithogenic particles (Yang et al, ). The sediment in the northern region of the study area is dominated by relatively higher fraction of coarser particles with lower clay fractions (~15%).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that 210 Pb ex is more effectively scavenged by particulate organic matter than fine lithogenic particles (i.e., clay) (cf. Moore and Dymondt 1988;Robbins and Edgington 1975;Oguri et al 2012;Yang et al 2015). In August 2012, Lu et al (2013) recorded an upwelling event east of the sill in the Narrows.…”
Section: Indications Of Riverine Inputs Focusing and Boundary Scavementioning
confidence: 99%